2013
DOI: 10.1002/dneu.22134
|View full text |Cite
|
Sign up to set email alerts
|

The role of Wnt/β‐catenin signaling in proliferation and regeneration of the developing basilar papilla and lateral line

Abstract: Canonical Wnt/β-catenin signaling has been implicated in multiple developmental events including the regulation of proliferation, cell fate, and differentiation. In the inner ear, Wnt/β-catenin signaling is required from the earliest stages of otic placode specification through the formation of the mature cochlea. Within the avian inner ear, the basilar papilla (BP), many Wnt pathway components are expressed throughout development. Here, using reporter constructs for Wnt/β-catenin signaling, we show that this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
86
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(95 citation statements)
references
References 89 publications
7
86
1
1
Order By: Relevance
“…Wnt/β-catenin signaling is required for proliferation in developing and regenerating neuromasts (26,48). Unexpectedly, the SPIA pathway analysis suggested that the Wnt/β-catenin pathway is inactive at 1 h after hair cell death (Table S3).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Wnt/β-catenin signaling is required for proliferation in developing and regenerating neuromasts (26,48). Unexpectedly, the SPIA pathway analysis suggested that the Wnt/β-catenin pathway is inactive at 1 h after hair cell death (Table S3).…”
Section: Resultsmentioning
confidence: 98%
“…Wnt/β-catenin signaling controls stem cell maintenance, quiescence, and proliferation during mammalian epithelial hair cell, zebrafish fin, mammalian intestine, hydra head, and planarian regeneration (82)(83)(84)(85)(86). Importantly, Wnt/β-catenin also is crucial for regulating proliferation in developing and regenerating zebrafish neuromasts (26,48).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, Wnt activators have been shown to increase the degree of regeneration after damage (Head et al, 2013;Jacques et al, 2014). Similarly, recent studies of the damaged neonatal mouse utricle revealed that Wnt/β-catenin activation increases both supporting cell proliferation and, subsequently, hair cell regeneration in vivo (Wang et al, 2015).…”
Section: Wnt Signalingmentioning
confidence: 95%
“…Conversely, inhibition of this signaling suppresses proliferation and causes a dramatic decrease in hair cell numbers [68,71]. Therefore, multiple recent studies have focused on regulating the Wnt pathway as a potential target for treating hearing loss [7,[71][72][73][74][75][76][77][78]. A recent study examined the role of epigenetic regulation in colorectal tumorigenesis and found that LSD1 activates the Wnt/β-catenin signaling pathway by downregulating a negative regulator of the pathway, Dickkopf-1 [79].…”
Section: Discussionmentioning
confidence: 96%
“…This stimulation of proliferation results in a significant increase in the number of hair cells within both developing and regenerating neuromasts. Conversely, inhibition of this signaling suppresses proliferation and causes a dramatic decrease in hair cell numbers [68,71]. Therefore, multiple recent studies have focused on regulating the Wnt pathway as a potential target for treating hearing loss [7,[71][72][73][74][75][76][77][78].…”
Section: Discussionmentioning
confidence: 98%